Novel Polyvinyl Alcohol/Starch Electrospun Fibers as a Strategy to Disperse Cellulose Nanocrystals into Poly(Lactic Acid) - Galotto-Lopez, M; Pereira-Abarca, A; Lopez de Dicastillo-Bergamo, A; Roa-Ruiz, K; Garrido-Ayala, L (Multidisciplinary Digital Publishing Institute (MDPI), 2017)
In this work, electrospun fibers of polyvinyl alcohol (PV) and starch (ST) were obtained to improve dispersion of cellulose nanocrystals (CNC) within a poly(lactic acid) (PLA) matrix with the aim of enhancing mechanical and barrier properties. The development and characterization of electrospun fibers with and without CNC, followed by their incorporation in PLA at three concentrations (0.5%, 1% and 3% with respect to CNC) were investigated. Morphological, structural, thermal, mechanical and barrier properties of these nanocomposites were studied. The purpose of this study was not only to compare the properties of PLA nanocomposites with CNC embedded into electrospun fibers and nanocomposites with freeze-dried CNC, but also to study the effect of electrospinning process and the incorporation of CNC on the PV and starch properties. SEM micrographs confirmed the homogenous dispersion of fibers through PLA matrix. X-ray analysis revealed that the electrospinning process decreased the crystallinity of PV and starch. The presence of CNC enhanced the thermal stability of electrospun fibers. Electrospun fibers showed an interesting nucleating effect since crystallinity of PLA was strongly increased. Nanocomposites with electrospun fibers containing CNC presented slightly higher flexibility and ductility without decreasing barrier properties. © 2017 by the authors.
Keywords: electrospinning; polyvinyl alcohol; starch; poly(acid lactic); cellulose nanocrystals